Mapping the nexus: a bibliometric analysis and social network analysis of transformative innovation policies and sustainable development goals - Falcone, P. M.; Tutore, I. (2025)
The pursuit of sustainable development has become a critical global objective, especially in light of increasing global challenges. The United Nations Sustainable Development Goals (SDGs), established in 2015, aim to address poverty, protect the environment, and ensure prosperity for all. Transformative innovation policies (TIPs) are emerging as vital strategies in achieving these goals by fostering systemic change rather than incremental improvements. TIPs are distinct because they seek to instigate profound transformations in sectors, societies, and economies, focusing on collaboration among diverse stakeholders. This manuscript aims to provide a comprehensive literature review and social network analysis to understand and highlights the interplay between TIPs and SDGs and elucidate business and management roles in advancing this global agenda. By analyzing existing research and visualizing the relationships within the literature, this study highlights the significant role of TIPs in advancing SDGs. The findings emphasize the necessity of innovative, inclusive, and purpose-driven approaches to reshape society toward sustainable and equitable development.